2020
DOI: 10.1038/s41598-020-67519-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA genomes revealed different patterns of high-altitude adaptation in high-altitude Tajiks compared with Tibetans and Sherpas

Abstract: High-altitude Tajiks (HA-Tajiks), Tibetans and Sherpas are three groups of high-altitude native people in China. The differences in the mtDNA genome between the three populations and the role of the mtDNA genome in the high-altitude adaptation of HA-Tajiks were seldom investigated. In this study, 80 HA-Tajiks were enrolled, and their whole mtDNA genomes were sequenced. The haplogroup of each subject was determined by comparison to the revised Cambridge Reference Sequence (rCRS). Ten additional populations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Therefore, vertebrate mitochondria play important roles in high‐altitude adaptation. Previous research has mainly focused on one kind or family of vertebrates, such as Tibetans (Chen et al, 2020), Tibetan pigs (Ma et al, 2019), Antilopinae (Hassanin et al, 2009), Galliform birds (Zhou et al, 2014), and Schizothoracine fishes (Li et al, 2013). However, previous research has not focused on different altitudes when assessing the five vertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vertebrate mitochondria play important roles in high‐altitude adaptation. Previous research has mainly focused on one kind or family of vertebrates, such as Tibetans (Chen et al, 2020), Tibetan pigs (Ma et al, 2019), Antilopinae (Hassanin et al, 2009), Galliform birds (Zhou et al, 2014), and Schizothoracine fishes (Li et al, 2013). However, previous research has not focused on different altitudes when assessing the five vertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The whole mitochondrial genome, that we are proposing as a novel taxonomic descriptor for its amount of genetic information and the relative ease in sequencing and annotation, is becoming widely used in phylogenomics and evolutionary studies [172][173][174] . Indeed, the resolutive power of the mitogenome was employed to disentangle systematic issues [175][176][177][178] .…”
Section: : E Alatus E Antarcticus E Balteatus E Charon E Crementioning
confidence: 99%
“…The Ethiopian patterns of hemoglobin concentration, oxygen saturation, and arterial oxygen content were found to be similar to those of low-altitude dwellers 19 . Apart from physiological differences, there exist specific polymorphisms belonging to mitochondrial genes ND3 and CYTB , which are believed to be associated with high-altitude adaptation in the Tajiks population in Tibet native to China 22 . It has been observed that genetic polymorphisms rarely impart their effect at phenotypic levels individually but as a cohort of multiple interactions together 23 .…”
Section: Introductionmentioning
confidence: 99%